Measuring the Effectiveness of Zakat in Alleviating Pakistanâ€™s Poverty: a Revisit - Abdullah, Naziruddin (International Journal of Engineering and Technology, 2018)
The article is written with the aim to investigate Pakistanâ€™s zakat effectiveness in alleviating poverty using an improvised index known as the Zakat Effectiveness Index (ZEIN).The study develops an index (ZEIN) to measure such effectiveness. The same Index can easily be extended to measure zakat effectiveness in other Muslim countries as well. In this paper Pakistan is selected from many Muslim countries for three reasons: first, the required data are available for computing ZEIN; second, to apply the newly developed version of zakat Index known as ZEIN; and, third, to revisit the performance of zakat recipients (the poor and needy) in the recent years and compared it with that of the previous years. Specifically, with the results are at our disposal the Pakistanâ€™s initiative to alleviate poverty using zakat as a tool can be measured. Unlike the previous study (Abdullah et at, 2015) where the Index had three (3) hypothetical cases, in the present study there is one (1) more hypothetical case being added to make it four (4). This is the first improvement made on the previous version of the index, namely the Basic Needs Deficiency Index (BDNI). The second improvement made is on the number of items included to the poor and needy expenditures on basic needs. While in the previously mentioned study the items included were five (5), namely food, clothing, housing (rental), medical and education, in this study one (1) more item, namely transportation, has been added to make it six (6). The third improvement made is related to the number of observations. While in the previous study only two (2) observations were made (2004/05 and 2005/06), the present study has been extended to include two more observations; 2007/08 and 2011/12. As such, the results and findings of the study are reckoned to be more conclusive. Specifically, the value of computed index has shown some improvements, although diminutive, implying that both the poor and needy were coping well to meet their consumption of basic needs. This study provides the policy makers in Pakistan to ascertain the effectiveness of zakat. Given this result, one policy implication emerges; zakat must be made mandatory by the government to the eligible zakat payers. The reason being, as zakat is the main source of â€œincomeâ€ to the needy and poor, clearly zakat helps them to improve their quality of life. Finally, work of this nature, to be best of our knowledge, has not been developed elsewhere.